Desenvolvimento e análise socioambiental da implantação de um biodigestor em uma propriedade rural - Fontes, Guilherme Emanuel Ferreira (Universidade Federal Rural do Semi-Árido, 2019)
The study was based on the implantation of an Indian-type biodigester adapted to a small rural property located in the city of Pau dos Ferros-RN, as a way of integrating agricultural activities into sustainable development. This biodigestor uses bovine manure to produce biofertilizers and renewable energy in the form of biogas, giving correct destination to the waste generated and contributing to the preservation of the environment. Some steps were adapted in its construction aiming at the lowest cost, and thus be economically viable in small rural properties. To identify and analyze the socio-environmental impacts, a matrix of interaction of the actions of the biodigestor with the impacts related to it was elaborated. This matrix evaluates the impacts divided in the environmental, social and economic fields with 6 attributes and 15 parameters that were interpreted and indicated a predominance of positive impacts in all of them, such as the production of renewable energy and biofertilizers, the decrease of the release of methane gas to atmosphere and eutrophication of water resources. In relation to the negative impacts, it can be stated that the water consumption for the maintenance of the biodigestor is weak due to the positive impacts associated with its use. These analyzes made it possible to reach the conclusion that the use of the proposed biodigester presents social and environmental feasibility for implantation in small properties, as it supplies the needs for which it was designated and presents positive impacts associated with its use.
Monografia
Keywords: Energia renovável; Renewable energies; Biogás; Biogas; Biofertilizante; Biofertilizer; Atividade rural; Rural activity; Impacto socioambiental; Socioenvironmental impact; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA